The Value of Obvious Empirical Results and the Omniscient Mr. Palans: Response to Mr. Palans' Comments - Theodore Eisenberg (Washington University Law Quarterly, 1994)
The Article did not defend this mode of work; perhaps I am too immersed in it to always keep in mind the merits of discussing the question. So let me spell out its benefits here.
Keywords: Bankruptcy; Lawyers – Fees; Bankruptcy reorganization